Evolution of scientific production on urban passenger transport: A bibliometric analysis - Domingo Verano-Tacoronte; Sandra Flores-Ureba; Margarita Mesa-Mendoza; Virginia Llorente-Mu\~noz (European Research on Management and Business Economics (ERMBE), 2024)
Urban passenger transport is a key point in the progress of any city. It is a strategic area whose efficient and sustainable development requires the incorporation of multiple disciplines. It affects territorial, social, health, economic, and environmental policies, among others. In recent years, we have witnessed a series of changes, especially in the domains of technology and environmental issues. The interdisciplinary nature of transport together with these developments has produced fundamental and far-reaching changes in the scientific production related to this field of study which is difficult to cover in a traditional review of the literature. The aim of this work is thus to conduct a bibliometric analysis of urban passenger transport during the period 2001-2021, which illustrates the advances made during this period and stimulate new research in this field. SciMAT software was used for this purpose. The results show the conceptual evolution of urban passenger transport research, identifying seven main thematic areas: (1) health and physical activity, (2) travel, (3) transport policy, (4) air pollution, (5) congestion, (6) social exclusion, and (7) electric and autonomous vehicles.
Keywords: R00; R41; R49; 650; Bibliometric analysis; Longitudinal analysis; Scientific maps; Urban passenger transport